The positive feedback loop between Nrf2 and phosphogluconate dehydrogenase stimulates proliferation and clonogenicity of human hepatoma cells. (1st December 2020) - Ong, Athena Jessica; Saeidi, Soma; Chi, Ngo Hoang Kieu; Kim, Su Jung; Kim, Do-Hee; Kim, Seung Hyeon; Park, Sin-Aye; Cha, Young-Nam; Na, Hye-Kyung; Surh, Young-Joon
Abstract: Recent studies report that nuclear factor-erythroid-2-related factor 2 (Nrf2) facilitates tumor progression through metabolic reprogramming in cancer cells. However, the molecular mechanism underlying the oncogenic functions of Nrf2 is not yet well understood. Some of the pentose phosphate pathway (PPP) enzymes are considered to play a role in the cancer progression. The present study was intended to explore the potential role of phosphogluconate dehydrogenase (PGD), one of the PPP enzymes, in the proliferation and migration of human hepatoma HepG2 cells. Genetic ablation of Nrf2 attenuated the expression of PGD at both transcriptional and translational levels. Notably, Nrf2 regulates the transcription of PGD through direct binding to the antioxidant response element in its promoter region. Nrf2 overexpression in HepG2 cells led to increased proliferation, survival, and migration, and these events were suppressed by silencing PGD . Interestingly, knockdown of the gene encoding this enzyme not only attenuated the proliferation and clonogenicity of HepG2 cells but also downregulated the expression of Nrf2. Thus, there seems to exist a positive feedback loop between Nrf2 and PGD which is exploited by hepatoma cells for their proliferation and survival. Treatment of HepG2 cells with ribulose-5-phosphate, a catalytic product of PGD, gave rise to a concentration-dependent upregulation of Nrf2. Collectively, the current study shows that Nrf2 promotes hepatoma cell growth and progression, partly through induction of PGD transcription.